Measuring attitude change in nursing students after completion of a First Nations peoples' health unit : Embedding a validated tool in learning and assessment practices. - McCullough, Kylie; Genoni, Angela; Murray, Melanie; Garvey, Darren; Coventry, Linda (Australian Journal of Indigenous Education v.53 n.1 https://doi.org/10.55146/ajie.v53i1.609, 2024)
The health inequities experienced by Aboriginal and Torres Strait Islander peoples, rooted in the historical and ongoing negative impacts of colonisation and disrupted traditional lifestyles, sees higher rates of illness and hospitalisations, increased morbidity and higher premature death rates than other Australians. Nurses represent the majority of Australia's health workforce and nursing students must have knowledge to provide culturally safe care to Australia's Aboriginal and Torres Strait Islander peoples. An Aboriginal and Torres Strait Islander Peoples' Health and Wellbeing unit was developed and introduced into an undergraduate nursing curriculum. This project aimed to determine the effectiveness of the unit content in changing the attitude of nursing students towards care of First Nations peoples. A quasi-experimental design was used and included all undergraduate nursing students commencing this unit in 2020 at one university in Western Australia. Students completed a validated questionnaire prior to engaging with unit learning materials and again at completion of the unit. Complete paired data was available for 339 participants. Results demonstrated statistically significant change in attitude following completion of the unit. Embedding targeted education concerning Aboriginal and Torres Strait Islander peoples' health and wellbeing positively influences attitudes in caring for this population of patients. [Author abstract]